CONTEMPORARY LITERATURE IN PARANÁ: : FEMALE AUTHORSHIP, IDENTITIES AND REPRESENTATION (Revista Crioula, 2022)
Women, as well as other minority groups, have been constantly silenced. Currently, the literary field is a space that makes these manifestations possible. This article is about contemporary literature of female authorship in Paraná from the analysis of some characters in the novel As filhas de Manuela (2017), by Paraná writer Bárbara Lia. We seek to discuss about contemporary literature of female authorship and turn our attention to the concepts of identity, exemplifying with passages about the character Manuela, and representation, emphasizing the two opposite extremes that permeate the traditional way of representing the woman: the angel-woman, which goes back to the figure of Maria (with the character Miquelina) and her antithesis, the woman linked to sin, often the prostitute, in reference to Eve expelled from Paradise (with the biological mother of the character Maria Teresa). Through this analysis, it is possible to understand that the writer from Paraná builds subversive characters, which contradict the canonical feminine representations. The theoretical framework is composed, mainly, by the texts of Agamben (2009) and Schollhammer (2009), discussing the concept of contemporary; Teixeira (2008, 2009) and Zolin (2009, 2019), approaching women's writing; Hall (2006) and Bauman (2005), reflecting on identities; Chartier (1991) and Dalcastagnè (2007, 2012), dealing with representation.